The effect of service quality and food quality on repurchase intention with customer satisfaction as a mediation variable - Faizah, Nurul; Abror (Marketing Management Studies, 2023)
The purpose of this study was to analyze the extent to which the influence of service quality and food quality and brand image on repurchase intentions, with satisfaction as a mediating variable for Richese Factory Transmart Padang consumers who are not known with certainty. In this study, a sample of 230 respondents was used using a purposive sampling method. The analysis technique used in SEM analysis uses smart PLS4. The results of the study are (1) service quality has a significant effect on repurchase intention at Richeece Factory Transmart Padang City. (2) service quality has a significant effect on Customer Satisfaction at Richeece Factory Transmart Padang City. (3) Food quality has a significant effect on customer satisfaction at Richeece Factory Transmart Padang City. (4) Food quality has a significant effect on repurchase intention at Richeece Factory Transmart, Padang City. (7) Customer Satisfaction has a significant effect on repurchase intention at Richeece Factory Transmart, Padang City.